Identification of redox‐sensitive cysteines in the Arabidopsis proteome using OxiTRAQ, a quantitative redox proteomics method. Issue 6 (28th January 2014) - Liu, Pei; Zhang, Huoming; Wang, Hai; Xia, Yiji
Abstract : Cellular redox status plays a key role in mediating various physiological and developmental processes often through modulating activities of redox‐sensitive proteins. Various stresses trigger over‐production of reactive oxygen/nitrogen species which lead to oxidative modifications of redox‐sensitive proteins. Identification and characterization of redox‐sensitive proteins are important steps toward understanding molecular mechanisms of stress responses. Here, we report a high‐throughput quantitative proteomic approach termed OxiTRAQ for identifying proteins whose thiols undergo reversible oxidative modifications in Arabidopsis cells subjected to oxidative stress. In this approach, a biotinylated thiol‐reactive reagent is used for differential labeling of reduced and oxidized thiols. The biotin‐tagged peptides are affinity purified, labeled with iTRAQ reagents, and analyzed using a paralleled HCD‐CID fragmentation mode in an LTQ‐Orbitrap. With this approach, we identified 195 cysteine‐containing peptides from 179 proteins whose thiols underwent oxidative modifications in Arabidopsis cells following the treatment with hydrogen peroxide. A majority of those redox‐sensitive proteins, including several transcription factors, were not identified by previous redox proteomics studies. This approach allows identification of the specific redox‐regulated cysteine residues, and offers an effective tool for elucidation of redox proteomes.